The effects of human capital on social capital: A cross-country analysis - Kevin J. Denny (University College Dublin, Department of Economics, 2003)
This paper uses two sets of cross-country micro datasets to analyse individuals' participation in voluntary and community activities and organisations. Analysing countries in the International Adult Literacy Survey and focusing on the impact of human capital I find a consistently positive effect of years of education on participation with the marginal effect of an additional year being around 2 or 3% for most countries. The effects are somewhat higher in English speaking countries. However controlling for functional literacy reduces this significantly with literacy accounting for around half the marginal effect of education. Labour market effects are generally very weak Using instrumental variables for a subset of countries we test and are unable to reject the hypothesis that education is exogenous. Using Eurobarometer data yields higher estimated impacts of schooling for most countries. It is also shown how attitudes towards the “third sector” predict higher participation in some forms of volunteering while a measure of religiosity often predicts more altruistic volunteering.
hdl:10197/938
Keywords: 330